Learning environments' activity potential for preschoolers (LEAPP): study rationale and design - Patricia Tucker; Leigh M. Vanderloo; Courtney Newnham-Kanas; Shauna M. Burke; Jennifer D. Irwin; Andrew M. Johnson; Melissa M. van Zandvoort (SAGE Publishing, 2013)
Background. The purpose of this paper is to provide an overview of the study protocol for the Learning Environments' Activity Potential for Preschoolers (LEAPP) study, the goal of which is to describe the activity levels of preschoolers attending various early learning venues and explore which attributes of these facilities (e.g. curriculum, policies, equipment, etc.) support activity participation. Design and Methods. This cross-sectional study aimed to recruit approximately 30 early learning environments requesting participation from preschoolers aged 2.5-5 years. Data collection included: Actical accelerometers (MiniMitter, Oregon, USA) to measure the activity levels of children for five consecutive days (15-second epoch length) while in care; the Environment and Policy Assessment and Observation tool to explore the early learning environment's impact on activity; anthropometric data; the Child Temperament Questionnaire to assess the influence of preschoolers' temperament on physical activity; and demographic information from parents/guardians and early learning staff. ANOVA and linear regression analyses will be conducted to assess variances in activity levels among preschoolers attending different early learning types and to explore the impact of early learning environments on their activity levels. Independent sample t-tests will be used to examine differences in activity levels based on sex and weight status. Expected impact of the study for public health. This research will provide the first Canadian data to address environmental influences on preschoolers' activity levels in differing early learning environments. Additionally, this work will highlight the extent to which activity levels vary among preschoolers enrolled in full-day kindergarten, centre-, and home-based childcare.